Profiles of Small Regulatory RNAs at Different Growth Phases of Streptococcus thermophilus During pH-Controlled Batch Fermentation - Liu, Gefei; Chang, Haode; Qiao, Yali; Huang, Kai; Zhang, Ao; Zhao, Yu; Feng, Zhen (Frontiers in Microbiology, 2021)
sRNA has been shown to play an important role under various stress conditions in bacteria, and it plays a vital role in regulating growth, adaptation and survival through posttranscriptional control of gene expression in bacterial cells. Streptococcus thermophilus is widely used as a starter culture in the manufacture of fermented dairy products. However, the lack of reliable information on the expression profiles and potential physiological functions of sRNAs in this species hinders our understanding of the importance of sRNAs in S. thermophilus. The present study was conducted to assess the expression profiles of sRNAs in S. thermophilus and to identify sRNAs that exhibited significant changes. A total of 530 potential sRNAs were identified, including 198 asRNAs, 135 sRNAs from intergenic regions, and 197 sRNAs from untranslated regions. Significant changes occurred in the expression of 238, 83, 194 and 139 sRNA genes during the lag, early exponential growth, late exponential growth and stationary phases, respectively. The expression of 14 of the identified sRNAs was verified by qRT-PCR. Predictions of the target genes of these candidate sRNAs showed that the primary metabolic pathways targeted were involved in carbon metabolism, biosynthesis of amino acids, ABC transporters, the metabolism of amino and nucleotide sugars, purine metabolism and the phosphotransferase system. The expression of the predicted target genes was further analyzed to better understand the roles of sRNAs during different growth stages. The results suggested that these sRNAs play crucial roles by regulating biological pathways during different growth phases of S. thermophilus. The present study provided valuable information for the functional study of sRNAs in S. thermophilus and indicated a future research direction for sRNA in S. thermophilus. Overall, our results provided new insights for understanding the complex regulatory network of sRNAs in S. thermophilus.